Difficulties encountered and coping strategies of Taiwanese special education graduate students in the Philippines - Hsiao, Man-Ping (Andrea) (Animo Repository, 2002)
The study describes the difficulties encountered and the coping strategies employed by the Taiwanese SPED graduate students. Specifically, it looked into the profile of these students in terms of gender, age, educational background, months of stay in the Philippines, and status of the respondents. It also determined if there was a significant relationship between the difficulties encountered and the coping strategies used. A three-part, 66-item questionnaire was used for this purpose - one part for the needed personal information, another for the difficulties encountered and the other for the coping strategies employed. The 57 participants were enrolled in De La Salle University and the Philippine Normal University. Findings indicate that majority of the participants were single, female, aged between 26-35 years, bachelor's degree holders and have been in the Philippines for 18-23 months. All the participants encountered difficulties in personal, academic, social and cultural aspects although generally these were considered as only a slight problem. They all made use of coping strategies for each of the categories of difficulties. It was found out that there is significant relationship between the difficulties encountered and the coping strategies used. The researcher offered the following recommendations: 1) The university where the Taiwanese SPED graduate students are enrolled must provide them with tutorial assistance, especially with regards to language learning. Facility in communication may lessen the academic and social problems of said students. 2) Counseling services be regularly offered to these students to help them cope with the difficulties they may encounter.